The effect of creatine supplementation on myocardial metabolism and function in sedentary and exercised rats - Webster, Ingrid (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Biomedical Sciences. Medical Physiology))--University of Stellenbosch, 2010.